A switchable stapled peptide. (19th January 2016) - Kalistratova, Aleksandra; Legrand, Baptiste; Verdié, Pascal; Naydenova, Emilia; Amblard, Muriel; Martinez, Jean; Subra, Gilles
Abstract: The O ‐ N acyl transfer reaction has gained significant popularity in peptide and medicinal chemistry. This reaction has been successfully applied to the synthesis of difficult sequence‐containing peptides, cyclic peptides, epimerization‐free fragment coupling and more recently, to switchable peptide polymers. Herein, we describe a related strategy to facilitate the synthesis and purification of a hydrophobic stapled peptide. The staple consists of a serine linked through an amide bond formed from its carboxylic acid function and the side chain amino group of diaminopropionic acid and through an ester bond formed from its amino group and the side chain carboxylic acid function of aspartic acid. The α ‐amino group of serine was protonated during purification. Interestingly, when the peptide was placed at physiological pH, the free amino group initiated the O‐N shift reducing the staple length by one atom, leading to a more hydrophobic stapled peptide. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : A switchable stapled peptide is reported. The staple includes a serine residue that may undergo an O‐N shift. The α‐amino group of serine was protonated during purification. Interestingly, when the peptide was placed at physiological pH, the free amino group initiated the O‐N shift reducing the staple length by one atom, leading to a more hydrophobic stapled peptide.